Effect of Air Inlet Hole Diameter of Venturi Tube on Air Injection Rate - Baylar, Ahmet; Ozkan, Fahri; Unsal, Mehmet (Springer, 2010)
The oxygen concentration in water is a prime indicator of the water quality for human use as well as for the aquatic biota. The physical process of oxygen transfer or oxygen absorption from the atmosphere acts to replenish the used oxygen. This process is termed re-aeration or aeration. Venturi aeration is a method of aeration that has become popular in recent years. A venturi tube allows air bubbles to be inserted into flowing water from air inlet holes and so increases oxygen levels in the water. In the present study, a series of experiments on venturi tubes were conducted to investigate the effect of air inlet hole diameter on air injection. It was observed from the results that air inlet hole diameter on venturi tube played a significant role in air injection and there was an optimal diameter that maximizes air injection. Moreover, a multiple non-linear regression equation was obtained for venturi tubes relating air flow and water flow to Reynolds number, inlet diameter and air inlet hole diameter.
Keywords: aeration; air injection; venturi; water quality